No‐Notice Urban Evacuations: Using Crowdsourced Mobile Data to Minimize Risk. Issue 1 (January 2014) - Oxendine, Christopher Edward; Waters, Nigel
Abstract Emergency evacuations during the past decade have transitioned from landline analog to mobile digital communication devices. Over 88% of US citizens own a mobile phone, providing a tool to enable better communication between first responders and citizens in order to minimize risk to evacuees during no‐notice evacuations. During an emergency, evacuees rely on social media to communicate with family, friends, and coworkers, often finding accessibility to social media more reliable than trying to make a phone call. Federal, state, and local emergency operations centers have made limited use of social media or Internet‐based communications to provide an alternative means for citizens to request assistance or provide information. Mobile devices provide an alternative method of incident reporting and analysis through volunteered geographic information (VGI), which first responders can use to minimize risk to evacuees.